Interoperability Types Classifications: A Tertiary Study - Santana Santos, Kécia Souza; Leoncio Pinheiro, Larissa Barbosa; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
Interoperability is the ability of heterogeneous systems to interact and exchange information efficiently and effectively through a planned process. Interoperability has several faces and usually, the syntactic interoperability type is pointed out as the most basic one for keeping information systems interoperable. Several other types of interoperability, such as semantics, pragmatics, syntactic, organizational have been addressed as important non-functional requirements for information systems. Still lacking consensus, there are several terms used to characterize interoperability. Thus, can bring confusion and ambiguity in the use of these terms, making it difficult to have a comprehensive view of related or similar interoperability proposals. While some primary studies address specific solutions for interoperability aspects, secondary studies seek to summarize some research directions and practical knowledge. This paper presents a tertiary study performed to investigate the current research state on interoperability, organizing knowledge that has already been defined, about types of interoperability known and the new ones. We conducted a tertiary study to achieve the stated goal based on a set of three research questions. The study identified selected and analyzed 15 secondary studies to answer the formulated research questions. Although twenty-seven different interoperability types were found, a specific subset is the most cited among these secondary studies. Its results can help to identify points that still require further investigation in the interoperability research field.